NAB2-STAT6 融合遺伝子の発現を認め中等度の転移リスクが示唆された上顎孤立性線維腫の1例 - 馬場, 貴; 鹿嶋, 光司; 山本, 哲彰; 山下, 善弘; 金氏, 毅; 福井, 丈仁 (日本口腔外科学会雑誌, 2024)
Solitary fibrous tumor（SFT） is a rare tumor in the oral region, and NAB2-STAT6 gene fusions are pathognomonic for SFT. Recently, various NAB2-STAT6 genotypes have been confirmed. This paper describes a case of a histologically rare metastasis of SFT with intermediate malignant potential that occurred in the maxillary gingiva. A 96-year-old woman visited our hospital because of swelling of the upper gingiva. Intra-oral examination revealed a well-defined elastic hard mass measuring 20×15×15 mm in the maxillary tuberosity. After several imaging examinations, a clinical diagnosis of benign tumor in the upper jaw was suggested. The lesion was surgically excised. Histological examination showed randomly arranged short spindle-shaped cells with indistinct, pale eosinophilic cytoplasm within a variably collagenous stroma, nuclear atypia, and five mitoses in ten high power fields. Immunohistochemical examination showed positive for STAT6, CD34, and CD99, and Ki-67 labeling index was 15%. The patient was considered to be at intermediate risk according to the 3-variable model for the prediction of metastatic risk. Genetic analysis showed NAB2 exon6-STAT6 exon 17 fusion gene. The histological diagnosis was SFT indicating intermediate malignant potential, but with intermediate risk of metastasis. No recurrence or metastasis have been observed in the five years following surgery.